The Trauma and Collective Memory Analyses of a Novel Titled “Semua Untuk Hindia” by Iksaka Banu - Una, Muna Alfadlilah (Universitas Tidar, 2025)
Memory receives various influences from the social background, starting from the surrounding community where the individual lives. Interactions between individuals, including with the community, foster memory. This shows that remembering requires a social context to materialize. One manifestation of memory is from individual trauma or collective trauma in a society. The source of memory is rooted in the collective material of human social products. Then, the memory develops and creates a correlation between people in society. One of the collective memories that prevails in Indonesia is the memory related to the struggle for independence. Society has a memory of the memories that occurred since the Dutch colonial era in Indonesia. This collective memory then becomes very interesting if explored with a theory that can see how unbroken the chain of memory in society is. The researcher then conducted research related to memory trauma in a collection of short stories by Iksaka Banu entitled “Semua Untuk Hindia” to see how the story responded to the traumas that occurred. This research uses informal data from a short story written by Iksaka Banu that tells a fictional story with a historical background, especially nostalgia for the colonial period. The method used in this research is descriptive qualitative which uses research and produces descriptive data in the form of written words such as dialog and sentences contained in novel. The qualitative method used is a descriptive method by presenting data as evidence that the author expresses collective memory in a novel. The results found that the author indirectly describes collective memory in the form of interrelated events during the Dutch colonization period.